Tekanan Orangtua, Perfeksionisme, dan Ketidakjujuran Akademik pada Pelajar di Jakarta - Luthfi Lusiane; Garvin (Fakultas Psikologi Universitas Pancasila, 2018)
Academic dishonesty is one phenomenon that has long happened in the world of education and is still interesting to study. It is known that academic dishonesty has increased dramatically each year in the past few decades. This study hypothesized that parental pressure and perfectionism are related to academic dishonesty. Data collection was carried out for 600 students in Jakarta between the ages of 14-18 years; using a questionnaire containing the Children-Adolescence Perfectionism Scale (CAPS), Perceived Parental Pressure Inventory (PPPI), and Academic Dishonesty Scale; all of these three were translated by researchers into Bahasa Indonesia before being used in research. Correlation test results showed that: (1) parental pressure is positively and significantly related to academic dishonesty, (2) perfectionism is positively and significantly related to academic dishonesty, and (3) parental pressure is positively and significantly related to perfectionism. This study suggested that parents should pay more attention to the child's condition and do not impose too high academic achievement standards so that children do not develop perfectionism and commit academic dishonesty to meet these standards.